(untitled) (Western Journal of Medical and Biomedical Sciences, 2024)
Orofacial soft tissue sarcomas (STSs) are malignant mesenchymal tumours in the oral and maxillofacial region. There has been only one primary study in Nigeria, and the epidemiology in Enugu, southeast Nigeria is unknown. The objective is to study the prevalence, distribution and features of orofacial soft tissue sarcomas at a tertiary hospital in Enugu, Southeast Nigeria. This is a 10-year (2012 to 2021) retrospective study of consecutive patients with orofacial soft tissue sarcomas presenting at a tertiary hospital in Enugu. Thirty-six (36) orofacial soft tissue sarcomas (STSs) were diagnosed out of 897 orofacial lesions. The prevalence among all orofacial biopsies, orofacial malignancies and orofacial sarcomas were 4.0%, 13.6%, and 76.6% respectively. Fibrosarcoma 36.1% (n=13) and rhabdomyosarcoma 19.4% (n=7) were most prevalent. Orofacial STSs presented a male to female ratio of 1.1 to 1, a mean age of 39.3 ± 19.7years, and were mostly diagnosed at the second and fifth decades, 25.2% (n=7). The mean age and duration among male patients were 33.8 ±19.9years, and 7.7 ± 6.7 months respectively, while for the female group: 44.7±18.1years and 11.1±6.9months respectively. The orofacial STSs were distributed as follows: mandible 36.1% (n=13), maxilla 33.3% (n=12), palate and cheek each had 8.3% (n=3). Pain 69.4% (n=25), bleeding 27.8% (n=10), and recurrence 19.4% (n=7) were often observed. In conclusion, orofacial STSs were infrequent and mostly involved the fibrous and skeletal tissues. The mean age of occurrence, especially among women is higher in Enugu.